TEKNIK MENARASIKAN PUISI SEBAGAI UPAYA MENINGKATKAN KREATIVITAS SISWA - Aquariza, Novi Rahmania (Jurnal Pena Indonesia, 2016)
In the effort of creating a joyful literary teaching, avoiding the boredom of both teachers and students, thus it needs the selection of a proper technique followed by the selection of a proper source too. Based on that statement, this article aimed to share the design of a proper technique and source which can be used in creating a joyful literary teaching. Hopefully it can stimulate the students creativity. In the beginning, this article serves the types of technique in literary teaching, especially for poetry. Then, this article also focused on the technique of poetry teaching which can be used as an effort to increase the students? creativity, that is narrating a poetry. The technique of narrating a poetry will be served by the supporting source.